Single gene defects leading to sperm quantitative anomalies. Issue 2 (22nd November 2016) - Mitchell, M.J.; Metzler‐Guillemain, C.; Toure, A.; Coutton, C.; Arnoult, C.; Ray, P.F.
Abstract : Azoospermia, defined by the absence of sperm in the ejaculate, is estimated to affect up to 1% of men in the general population. Assisted reproductive technologies have revolutionized the treatment of infertility, and some azoospermic men, those with a post‐meiotic defect, can conceive following the use of viable spermatoza recovered from testicular or epididymal biopsies. Although male infertility is a multifactorial disease, it is believed that genetic factors are predominant in the etiology of azoospermia and severe oligozoospermia. Despite that assumption, substantiated by the high number of infertile knockout (KO) mice and the even higher number of genes expressed essentially in the testis, little is known about the pathophysiology of reduced sperm production, its primary causes or the genetic and epigenetic consequences for the gamete and the future conceptus. The identification of genetic abnormalities is therefore paramount to understand spermatogenesis, to adopt the best course of action for the patient and to provide adequate genetic counseling. We provide here a review of the recent literature on the genetics of azoospermia and oligozoospermia, focusing on defects directly altering sperm production. New sequencing technologies are contributing to the rapid evolution of the recent field of infertility genetics. Abstract :